Mapping techniques applied to the study of São Paulo city architectonic epigraphy - Farias, Priscila Lena; Gouveia, Anna P. S.; Pereira, André L. T.; Gallo, Haroldo; Gatto, Patrícia S. (InfoDesign, 2008)
This paper summarizes some findings of a research on typographic elements found in São Paulo city central area. Using mapping methodology, we show that based on the information found in certain inscriptions in the building façades, it is possible to identify patterns and paths of settlement in this area, specially in what regards authorship and dates of design and construction. Although many of the edifices studied are part of the city heritage, heritage files very often lack this kind of information, which can be found in architectonic epigraphs. Defined as signatures, public and everlasting records of design authorship, epigraphs might also be analyzed as an example of visual design applied to the city.